Vpliv glasbe med bronhoskopijo na bolnikovo počutje - Primožič Petrinec, Marija (Obzornik zdravstvene nege, 2006)
Bronchoscopy is one the most often used invasive methods in puhmology. It is most often used in diagnostics of pulmonary cancer. Before the proceedings, patients are usually scared and alarmed, they are afraid of the method itself,possible pain and the results. Patient''s fear and anxiety are managed with the help of different anxiolytics. One of the most important parts of theprocess is the preparation of the patient for the proceeding which often takes the form of written instructions or oral explanation. In KOPA Golnik, the patients are shown a videotape of the proceeding. During the proceeding, the patient is calmed by a relaxed approach of the staff and clear instructions about possible complications. Professional literature abounds of data that music during invasive proceedings affects patient''s sensations in a positive way, diminishes fear and enhances his cooperation during the process,as well as prevents certain complications during the process and afterwards. We tried to find out whether music during bronchoscopy really diminishes anxiety and fear. In order top find out, a prospective, randomized study was carried out which cowered 200 patients. The anonymous questionnaire was filled in with the help of the nurses who also took notes of physiologicalparameters during the proceeding. The research study revealed that music has a calming effect on the patients: patients who listened to music during bronchoscopy had much lower blood pressure and pulse than the control group. By measuring physiological parameters, calming effect of music on patient''s sensations has been indirectly proven.
Keywords: Blood Pressure; bolniki; Bronchoscopy; Bronhoskopija; Glasba; Krvni pritisk; Music; počutje; Pulse; Pulz